What can a geography as dancing body? language-experience ’gesture-movement-affection’ (fragments) - Queiroz Filho, Antonio Carlos (Geografares, 2016)
Made of fragments, this paper proposes to think about relations and possible repercussions existing between language and experience from the perspective of some post-structuralist authors. I sought in reflection about body and dance a way to discuss this issue and at the same time, making a geography as something that produces in us affections. “What can a Geography as dancing body?” is beyond a question, an invitation, a proposition: a ballerina geography